Oil Price Volatility Shocks and the Macroeconomic Indicators: Evidence from Saudi Arabia - Darshita Fulara Gunwant; Sartaj Rasool Rather; Faisal Nazir Zargar (International Journal of Energy Economics and Policy)
This study investigates whether the positive and negative shocks in oil price volatility have an asymmetric effect on the volatility measures of the macroeconomic variables in the context of Saudi Arabia- a major oil exporting country in the region.  The empirical results suggest that a positive shock in the oil price volatility tends to generate higher volatility in inflation, forex reserves, public spending and stock prices, whereas a negative shock in the oil price volatility does not seem to have any significant impact on the volatility measures of most of these variables. The crucial inference that emerges from these findings is that the unfavourable events in the oil markets that cause higher volatility in oil prices seem to generate higher macroeconomic uncertainty. However, the favourable oil market events that are believed to reduce uncertainty, do not seem to have a stabilizing impact on the macroeconomic environment of the Saudi economy.